Hubungan antara Motivasi Berwirausaha dengan Sikap Kewirausahaan bagi Mahasiswa Jurusan Teknik Otomotif Fakultas Teknik Universitas Negeri Padang - Nuzul Hidayat; Ganefri Ganefri; Asmar Yulastri; Muslim Muslim; Muhammad Yasep Setiawan (AEEJ : Journal of Automotive Engineering and Vocational Education, 2022)
The purposes of this study are to (1) describe the entrepreneurial spirit of automotive engineering students, (2) describe the motivation of the entrepreneurial spirit of automotive engineering students, and (3) see whether entrepreneurship and motivation have a relationship between For automotive engineering students This research is a descriptive analysis research. , regression and correlation, data collection was carried out using questionnaires and literature studies as additional data. In this study, the sample was 8th semester students as many as 35 students. Survey Results (1) The level of student entrepreneurship attitude for entrepreneurship is 71.36% in the "good" category. (2) while for motivation in entrepreneurship with a value of 76.64% with a level of "good" category. (3) Analyzing the relationship between entrepreneurship and entrepreneurship with product moment, obtained a score of 0.655, with a coefficient of determination of 53.40%, and it is known that the variable for attitude to entrepreneurship has an influence with the motivation variable for entrepreneurship with a value of 54.40%, and which has other influences. is the personal ability of students, environmental conditions, family and friends around them